Potensi Pengembangan Desa Wisata dalam Meningkatkan Pendapatan Masyarakat dengan Menggunakan Analisis SWOT di Desa Pematang Serai Langkat - Marini, Yushita; Marina, Nisha; Arnita, Vina (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to identify and develop the potential of Pematang Serai village as a tourist village through a SWOT analysis. Pematang Serai Village is one of the villages that has the beautiful natural charm of the coastal area of the Langkat river, making the village a potential tourism village which then the BUMDes business unit designed the Getek Online (Geol) natural tourist attraction. In 2021, the Langkat Regency Government inaugurated the Sustainable Tourism Village (Kejutan Dewi) Nature Tourism Geol Pematang Serai Village, promoting and improving traditional markets in the tourist village so that it becomes the village's identity. These problems focus on the not maximal potential of the village which has been developed as a tourism village in increasing the income of its people. To approach this problem, a reference to SWOT analysis theory is used in finding the potential of a tourist village and the constraints faced by the village. Data collected through the interview method (primary data) to village business actors and BUMDes in Pematang Serai Village and secondary data related to village data were analyzed qualitatively. This study concluded that from the SWOT analysis, namely by analyzing the strengths, weaknesses, opportunities and threats of planning and strategies in obtaining income, the village of Pematang Serai can increase the income of its people by developing village potential from strategic variable concepts, market competitiveness, marketing concepts, village promotions.